Types and Abundance of Marine Debris along the Coasts of Tanjung Datu National Park-Samunsam Wildlife Sanctuary - Ruhana, Hassan; Muhammad Nur Arif, Othman (UNIMAS Publisher, 2024)
Marine debris or marine litter is human-created waste that has deliberately or accidentally been released to the sea, frequently washing aground and stranded on beaches. Beaches along Tanjung Datu National Park to Samunsam Wildlife Sanctuary (TDNP-SWS) suffer marine debris problem, which reduced the aesthetic value of the landscape, consequently gives negative impact to the eco-tourism industry. To date, there is no documentation yet on the types and abundance of marine debris stranded on beaches of TDNP-SWS. Hence, this study was conducted to obtain the information on types and abundance of marine debris stranded on four selected sandy beaches along the coasts of TDNP-SWS. Field samplings were performed in August 2018, following standard protocols – debris collection, sorting into categories, enumeration and finally data analysis. The most abundant marine debris was plastics followed by paper, aluminium, rubber, glass and metal. Beach of Kampung Telok Melano had the highest number of plastic debris (606 item/km) followed by Kampung Telok Serabang (473 item/km), SWS (130 item/km) and TDNP (43 item/km). The data shown here is just a ‘snap shot’ of marine debris problem along TDNP-SWS coastline in 2018, prior to the official opening of Pan Borneo Highway, connecting Kampung Telok Melano to Sematan. Further studies need to be done in order to gain information on spatial and temporal marine debris in the area, where the information could help relevant agencies to formulate marine debris management as it is the basis to promote healthy living condition for local people and to ensure sustainable ecotourism in TDNP-SWS area.